2006
DOI: 10.1002/hep.21197
|View full text |Cite|
|
Sign up to set email alerts
|

Duration of peginterferon therapy in acute hepatitis C: A randomized trial

Abstract: Spontaneous resolution of acute hepatitis C virus infection cannot be predicted, and chronic evolution of the disease occurs in a majority of cases. To assess the efficacy and safety of peginterferon alpha-2b administered for 8, 12, or 24 weeks in patients with acute hepatitis C virus infection a total of 161 patients were identified with acute hepatitis C virus infection. Of these, 30 patients refused treatment but were retained in the study as a nonrandomized comparison group. Of the 131 patients who consent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 31 publications
4
90
2
1
Order By: Relevance
“…The results reported from Italy 1 are not in line with experiences in Switzerland showing that barriers to interferon-alpha therapy are higher in intravenous drug users than in other patients with acute hepatitis C. 2 We have to stress that patients with ongoing drug abuse were excluded from our study. 3 Nevertheless, our experiences in patients with previous drug abuse are also more in line with the Swiss data than with the study by de Rosa et al demonstrating the importance of thorough patient selection and close monitoring during therapy in the treatment of acute hepatitis C.…”
Section: Replysupporting
confidence: 86%
See 2 more Smart Citations
“…The results reported from Italy 1 are not in line with experiences in Switzerland showing that barriers to interferon-alpha therapy are higher in intravenous drug users than in other patients with acute hepatitis C. 2 We have to stress that patients with ongoing drug abuse were excluded from our study. 3 Nevertheless, our experiences in patients with previous drug abuse are also more in line with the Swiss data than with the study by de Rosa et al demonstrating the importance of thorough patient selection and close monitoring during therapy in the treatment of acute hepatitis C.…”
Section: Replysupporting
confidence: 86%
“…Moreover, the effectiveness of late treatment administered for 8, 12 and 24 weeks was investigated in another study recently published in HEPATOLOGY and showed that the SVR rate increased with the duration of treatment. 3 The SVR rates, when AHC was treated for 8, 12 and 24 weeks, were 67.6%, 82.4% and 91.2%, respectively.Further proof of the importance for early treatment is that negative plasma HCV-RNA was observed 2.5 weeks after the beginning of treatment. We believe this length of time may be shortened since our patients received a variable dosage of PEG-IFN ranging from 1.06 to 1.66 g/Kg/weekly.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Genotype 4 was nearly as common as genotype 1 and had the highest response (100% SVR) in the 24-week treatment group. 128 In a second study, Kamal et al 129 followed patients for 8 weeks after the identification of acute HCV. Subjects were then randomized to receive pegylated interferon alpha 2b, beginning at 8, 12, or 20 weeks, and they underwent a 12-week treatment regimen.…”
Section: Treatment Of Acute Hcv Infectionmentioning
confidence: 99%
“…A shorter treatment duration may be considered for patients infected with HCV genotypes 2 and 3 with a rapid viral response (RVR), i.e. undetectable HCV RNA at treatment week 4 [14].…”
Section: Treatment Recommendations For Adult Patientsmentioning
confidence: 99%